2018
DOI: 10.1093/carcin/bgy050
|View full text |Cite
|
Sign up to set email alerts
|

Statin use linked with a decrease in the conversion from high-grade prostatic intraepithelial neoplasia (HGPIN) to prostate cancer

Abstract: The roles of obesity, metabolic dysregulation and systemic inflammation to advance prostate carcinogenesis are unclear. This study investigates metabolic and inflammatory factors in the transition from high-grade prostatic intraepithelial neoplasia (HGPIN) to prostate cancer (PC). We prospectively followed 160 men diagnosed with HGPIN at biopsy and therefore at high-risk and clinically monitored for PC. Analyses investigated body mass index (BMI), waist circumference, waist-hip ratio (WHR), height, fat mass, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Recently, statin usage has been linked to a reduced risk of prostate cancer death, improved recurrence-free survival after radical treatment [ 1 , 4 , 5 ], decreased risk of advanced prostate cancer, and decreased risk of conversion of high-grade intraepithelial neoplasia to prostate cancer [ 12 ]. Also, a recent study published by Longo et al found fluvastatin to induce PCa cell death in vitro [ 13 ]. There are few studies assessing statins’ effect on ADT-treated patients [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, statin usage has been linked to a reduced risk of prostate cancer death, improved recurrence-free survival after radical treatment [ 1 , 4 , 5 ], decreased risk of advanced prostate cancer, and decreased risk of conversion of high-grade intraepithelial neoplasia to prostate cancer [ 12 ]. Also, a recent study published by Longo et al found fluvastatin to induce PCa cell death in vitro [ 13 ]. There are few studies assessing statins’ effect on ADT-treated patients [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…grade intraepithelial neoplasia to prostate cancer [12]. Also, a recent study published by Longo et al found fluvastatin to induce PCa cell death in vitro [13]. There are few studies assessing statins' effect on ADT-treated patients [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other measures, BMI is readily available in the medical record and easily computed upon physical exam. BMI also predicts prostate cancer outcomes [ 4 , 5 , 28 30 ] and is associated with health outcomes in a trajectory similar to other measures of adiposity [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%